PENDEKATAN SAINTIFIK-ICM BERBASIS LKPD TINGKATKAN HASIL BELAJAR IPS MATERI EKONOMI KREATIF PADA KELAS IXD SMPN 3 CEPIRING - HERLINA HERLINA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of this study is to describe the application of the LKPD-based Scientific-Index Card Match (ICM) approach in learning social science material for Creative Economy in class IXD SMPN 3 Cepiring Even Semester in the 2021/2022 academic year and to find out the increase in social studies learning outcomes for Creative Economy material in class IXD SMPN 3 Cepiring. Even Semester of the 2021/2022 Academic Year, through the application of the LKPD-based Scientific-Index Card Match (ICM) approach. This type of research is classroom action research, which is carried out in two cycles. Each cycle consists of 4 stages, namely planning, implementing actions, observing and reflecting. This research was conducted at SMPN 3 Cepiring, Kangkung sub-district, Kendal district, Central Java. The research subjects were 24 students in class IXD, consisting of 12 boys, 12 girls and Herlina, SE, a social studies teacher for class IXD at SMPN 3 Cepiring. Data collection techniques in the form of observation of teacher skills, spiritual and social attitudes, written tests, oral tests, and assignments as well as documentation in the form of photos of the learning process. The indicator of the success of this research is if the LKPD-based scientific approach-Index Card Match (ICM) in class IXD SMPN 3 Cepiring Even Semester 2021/2022 can be applied with good criteria, and is able to improve learning outcomes of attitude competence with good predicates, knowledge competence and skills KKM school (75). The results of this study show that the LKPD-based Scientific-Index Card Match (ICM) approach was successfully applied in social studies learning material for Creative Economy in class IXD SMPN 3 Cepiring Even Semester for the 2021/2022 academic year, with good success rate criteria, and the application of the Scientific-Index Card approach. The LKPD-based Match (ICM) succeeded in increasing the completeness of social studies learning outcomes for Creative Economy materials in class IXD of SMPN 3 Cepiring in the even semester of the 2021/2022 academic year. namely: increasing mastery of learning outcomes of spiritual attitudes and social attitudes by 33.34, increasing mastery of learning outcomes of knowledge competence by 29.17%, increasing mastery of learning outcomes of skills competence by 25.00%. The conclusion of this study is that the LKPD-based Scientific-Index Card Match (ICM) approach has succeeded in increasing mastery of Social Science learning outcomes for Creative Economy Class IXD SMPN 3 Cepiring Even Semester for the 2021/2022 Academic Year. Therefore, it is recommended to use the LKPD-based Scientific-Index Card Match (ICM) approach in the learning process, especially social studies learning. ABSTRAKTujuan Penelitian ini memaparkan penerapan pendekatan Saintifik-Index Card Match (ICM) berbasis LKPD dalam pembelajaran IPS materi Ekonomi Kreatif pada kelas IXD SMPN 3 Cepiring Semester Genap Tahun Pelajaran 2021/2022 dan mengetahui peningkatan hasil belajar IPS materi Ekonomi Kreatif pada kelas IXD SMPN 3 Cepiring Semester Genap Tahun Pelajaran 2021/2022, melalui penerapan pendekatan Saintifik-Index Card Match (ICM) berbasis LKPD. Jenis Penelitian yang dilakukan adalah penelitian tindakan kelas, yang dilakukan dalam dua siklus. Tiap siklus terdiri dari 4 tahap yaitu perencanaan, pelaksanaan tindakan, observasi dan refleksi. Penelitian ini dilakukan di SMPN 3 Cepiring, kecamatan Kangkung kabupaten Kendal, Jawa Tengah dengan subjek penelitian peserta didik kelas IXD berjumlah 24 orang, terdiri atas 12 orang laki-laki, 12 orang perempuan dan Herlina, SE guru IPS kelas IXD SMPN 3 Cepiring. Teknik pengumpulan data berupa observasi keterampilan guru, sikap spiritual dan sosial, tes tertulis, tes lisan, dan penugasan serta dokumentasi berupa foto proses pembelajaran. Indikator keberhasilan penelitian ini adalah apabila pendekatan saintifik-Index Card Match (ICM) berbasis LKPD di kelas IXD SMPN 3 Cepiring Semester Genap Tahun Pelajaran 2021/2022 dapat diterapkan dengan kriteria baik, dan mampu meningkatkan hasil belajar kompetensi sikap dengan predikat baik, kompetensi pengetahuan dan keterampilan ? KKM sekolah (75). Hasil penelitian ini menunjukan pendekatan Saintifik-Index Card Match (ICM) berbasis LKPD berhasil diterapkan dalam pembelajaran IPS materi Ekonomi Kreatif pada kelas IXD SMPN 3 Cepiring Semester Genap Tahun Pelajaran 2021/2022, dengan kriteria tingkat keberhasilan baik, dan penerapan pendekatan Saintifik-Index Card Match (ICM) berbasis LKPD berhasil meningkatkan ketuntasan hasil belajar IPS materi Ekonomi Kreatif pada kelas IXD SMPN 3 Cepiring Semester Genap Tahun Pelajaran 2021/2022. yaitu: peningkatan ketuntasan hasil belajar kompetensi sikap spiritual dan sikap sosial sebesar 33,34, peningkatan ketuntasan hasil belajar kompetensi pengetahuan sebesar 29,17%, peningkatan ketuntasan hasil belajar kompetensi keterampilan sebesar 25,00%. Simpulan penelitian ini bahwa pendekatan Saintifik-Index Card Match (ICM) berbasis LKPD berhasil meningkatkan ketuntasan hasil belajar IPS Materi Ekonomi Kreatif kelas IXD SMPN 3 Cepiring Semester Genap Tahun Pelajaran 2021/2022. Oleh karena itu disarankan penggunaan pendekatan Saintifik-Index Card Match (ICM) berbasis LKPD dalam proses pembelajaran khususnya pembelajaran IPS.